Cohesión entre Ontologías: una técnica para medir integración semántica - Vitturini, Mercedes (2011)
Multiple SIG ontologies are accessible on the Web. Beside, each application has its own data model or application ontology. Ontology mapping could provide a common layer from which several ontologies could exchange information in a semantically manners. In this article we present a new technique that could collaborate with measuring cohesion among ontologies and could anticipate the integration result of these.